2003
DOI: 10.1002/art.10719
|View full text |Cite
|
Sign up to set email alerts
|

The effect of HLA–DR on susceptibility to rheumatoid arthritis is influenced by the associated lymphotoxin α–tumor necrosis factor haplotype

Abstract: Objective. HLA-DRB1, a major genetic determinant of susceptibility to rheumatoid arthritis (RA), is located within 1,000 kb of the gene encoding tumor necrosis factor (TNF). Because certain HLA-DRB1*04 subtypes increase susceptibility to RA, investigation of the role of the TNF gene is complicated by linkage disequilibrium (LD) between TNF and DRB1 alleles. By adequately controlling for this LD, we aimed to investigate the presence of additional major histocompatibility complex (MHC) susceptibility genes.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

2004
2004
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 36 publications
0
35
1
Order By: Relevance
“…Several previous studies have reported associations in the telomeric class III region, independent of HLA-DRB1, particularly centred on the lymphotoxin a, and tumour necrosis factor-a loci. [31][32][33][34][35] Our WGA scan data did not provide evidence for association with RA of SNPs in this region (all zo0.8), but did demonstrate association with SNPs in and around loci encoding components of the complement pathway, complement component C2 and complement factor B. Previous studies that have demonstrated association in and around these loci have not been able to consistently show that association is independent of the HLA-DRB1*04 haplotype.…”
Section: à5contrasting
confidence: 88%
See 1 more Smart Citation
“…Several previous studies have reported associations in the telomeric class III region, independent of HLA-DRB1, particularly centred on the lymphotoxin a, and tumour necrosis factor-a loci. [31][32][33][34][35] Our WGA scan data did not provide evidence for association with RA of SNPs in this region (all zo0.8), but did demonstrate association with SNPs in and around loci encoding components of the complement pathway, complement component C2 and complement factor B. Previous studies that have demonstrated association in and around these loci have not been able to consistently show that association is independent of the HLA-DRB1*04 haplotype.…”
Section: à5contrasting
confidence: 88%
“…Previous studies that have demonstrated association in and around these loci have not been able to consistently show that association is independent of the HLA-DRB1*04 haplotype. 36,37 However, taken together, data generated by us and others [30][31][32][33][34][35]38,39 strongly suggest multiple RA susceptibility loci within the HLA region, with the HLA class II association the strongest. A comprehensive HLA SNP genotyping experiment is warranted in RA, using sufficiently large cohorts to enable detection of effects independent of HLA-DRB1.…”
Section: à5mentioning
confidence: 92%
“…The relevance, though not the function, of HLA antigens to disease is well recognized 140,141 and may account for many of those studies that find positive evidence of association to TNF, emphasizing the role of TNF variants as markers for HLA or other disease loci located in the MHC. 136,142 The strong evidence for the presence of other risk loci within the MHC besides the known HLA alleles may account for associations after discounting linkage to known HLA risk genes.…”
Section: Disease Associations-conclusionmentioning
confidence: 99%
“…These results strongly support the presence of an additional MHC susceptibility locus or loci outside of the TNF region. 34 However, as the knowledge of the haplotype structure of this area is currently limited further, large studies are necessary to rule out the LT-TNF region definitively.…”
Section: -30mentioning
confidence: 99%